The Desire for Sovereignty – An Explanation of EU Attitudes in the Arab World†. (22nd September 2016) - Isani, Mujtaba; Schlipphak, Bernd
Abstract: A growing body of survey research shows that the European Union (EU) has a relatively benign image around the world, except among Arab populations. What informs Arab citizens' sceptical attitudes toward the European Union (EU)? Combining literature on Arab public opinion and perceptions of the EU, we argue that Arab citizens' feelings about the EU are influenced most prominently by their desire for sovereignty. Moreover, traditional utilitarian and cue‐taking mechanisms should also impact Arab EU attitudes. We empirically test our argument using data from the third wave of the Arab Barometer (AB). Our findings confirm that Arab citizens' EU views seem to be informed by their desire for sovereignty, as well as economic considerations and trust in domestic elites. Having provided evidence on Arab opinions about the EU, we discuss relevant theoretical and methodological directions for future research.